Cumulative Software Failures To Erp Systems (International Journal of Engineering and Computer Science, 2014)
Software failures usually can be defined as a delivery service mechanism failure when a system usually does not agree for expected service or function as desired. According to Laprie it can be said as failures to systems usually occur when delivered service no longer compiles with the specifications, the definition is applicable to both hardware & software system failures